ELEVATED BIOMARKERS AS CRP, BNP AND/OR MICROALBUMIN IN ASYMPTOMATIC OBESE SUBJECTS MIGHT BE CLUE FOR PERIVASCULAR/EPICARDIAL ADIPOSITY WHICH MANDATES FURTHER CARDIOVASCULAR EVALUATION. - Antonella Sabatini (Elsevier, 2024)
Therapeutic Area: Novel Biomarkers Background: Perivascular/cardio-adiposity have been reported to be cardiovascular risk markers. Purpose: To assess whether elevated biomarkers such as CRP and BNP and/or microalbumin in asymptomatic obese subjects are associated with elevated epicardial fat volume/perivascular adiposity contributing to structural and functional abnormalities such as abnormally elevated C2, abnormal blood pressure post exercise, abnormal CIMT and elevated calcium score. Methods: 330 asymptomatic obese subjects were screened for cardiovascular risk assessment using the Early Cardiovascular Disease Risk Scoring System (ESCVDRS) known as Rasmussen Risk Score (RRS), previously reported. The ESCVDRS includes 7 vascular and 3 cardiac tests. Among the additional test, CRP, proBNP, microalbumin were also measured. Coronary calcium score and epicardial fat volume was measured utilizing cardiac CT Siemens Somatom Definition Dual source CT scanner 64x2. Out of the 330s subjects, 55 showing objective high coronary calcium score were divided into 2 groups according to epicardial fat volume levels: Group A, 33 subjects with high epicardial fat volume and high calcium score; Group B, 22 subjects with high calcium score but normal epicardial fat volume. Results: Results are shown on table below. Subjects with elevated EFV have elevated CAC and biomarkers in addition to structural and functional abnormalities.As for the early screening for early cardiovascular subclinical atherosclerosis, mandating early detection and intervention, subjects with elevated epicardial fat volume have significantly elevated coronary calcium score associated with significant elevation in biomarker such as BNP, CRP and microalbumin in addition to structural and functional abnormalities. In addition, abnormal rise in blood pressure post exercise. It is of interest to note that subjects with elevated epicardial fat volume have more ECG abnormalities as compared with subject was normal epicardial fat volume. Conclusions: 1. Abnormal biomarkers such as CRP, BNP and/or microalbumin even in asymptomatic subjects might be the clue for abnormally elevated epicardial fat volume which is a novel risk marker associated with significant structural and functional abnormalities. 2. Elevated biomarkers mandate early screening for cardiovascular structural and functional abnormalities, particularly excess epicardial fat volume, implementing treatment to avoid any future complications. Early detection to protect.